Respiratory‐induced 3D deformations of the renal arteries quantified with geometric modeling during inspiration and expiration breath‐holds of magnetic resonance angiography. Issue 6 (1st April 2013) - Suh, Ga‐Young; Choi, Gilwoo; Draney, Mary T.; Herfkens, Robert J.; Dalman, Ronald L.; Cheng, Christopher P.
<x xml:space="preserve">Abstract</x> Purpose To quantify renal artery deformation due to respiration using magnetic resonance (MR) image‐based geometric analysis. Materials and Methods Five males were imaged with contrast‐enhanced MR angiography during inspiratory and expiratory breath‐holds. From 3D models of the abdominal aorta, left and right renal arteries (LRA and RRA), we quantified branching angle, curvature, peak curve angle, axial length, and locations of branch points. Results With expiration, maximum curvature changes were 0.054 ± 0.025 mm−1 (P < 0.01), and curve angle at the most proximal curvature peak increased by 8.0 ± 4.5° (P < 0.05) in the LRA. Changes in maximum curvature and curve angles were not significant in the RRA. The first renal bifurcation point translated superiorly and posteriorly by 9.7 ± 3.6 mm (P < 0.005) and 3.5 ± 2.1 mm (P < 0.05), respectively, in the LRA, and 10.8 ± 6.1 mm (P < 0.05) and 3.6 ± 2.5 mm (P < 0.05), respectively, in the RRA. Changes in branching angle, axial length, and renal ostia locations were not significant. Conclusion The LRA and RRA deformed and translated significantly. Greater deformation of the LRA as compared to the RRA may be due to asymmetric anatomy and mechanical support by the inferior vena cava. The presented methodology can extend to quantification of deformation of diseased and stented arteries to help renal artery implant development. J. Magn. Reson. Imaging 2013;38:1325–1332. © 2013 Wiley Periodicals, Inc.